A protein biosensor that relies on bending of single DNA molecules. - Crawford, R; Kelly, D; Kapanidis, A (2012)
A "bendy" protein sensor: A DNA-based sensor that uses folded DNA (through DNA kinks) and protein-induced bending to detect DNA-binding proteins is presented. Single-molecule sensing of a transcriptional activator (catabolite activator protein, CAP, which bends its DNA site by 80°) is demonstrated in solution and on surfaces, both in buffers and in cell lysates. The method should allow detection of a wide range of DNA-bending proteins.